TECHNOLOGICAL PROPERTIES OF Eucalyptus grandis USING DIGITAL IMAGE CORRELATION (DIC) - Stupp, Angela Maria; Matos, Jorge Luis Monteiro de; Argenta, Marco André; Cunha, Alexsandro Bayestorff da (Floresta, 2024)
This study aimed to characterize some technological properties of Eucalyptus grandis wood and evaluate the use of Digital Image Correlation (DIC) to obtain the displacement and the behavior of the samples in deformation and its relationship with tension in tensile and compression tests parallel to the fibers. Samples were produced from 23-year-old wood to determine the basic density, shrinkage coefficient, anisotropy in contraction and swelling, and the mechanical strength to tensile and compression parallel to the fibers. To calculate the Modulus of Elasticity (E), the stress wave velocity was measured in the tensile samples. The measurement of sample elongation during the test was obtained by DIC and then calculating strain and E. The basic density was 0.497 g/cm³ and the anisotropy values of contraction (1.25) and swelling (1.27) indicated that it was a very dimensionally stable wood. The tensile strength (118.50 MPa) was higher than normally obtained for the species. The parallel compression average values (53.06 MPa) were similar to those in the literature. As for E, the average value obtained by DIC was 12,664.24 MPa; by the stress wave timer, it was 11,941.35 MPa. The evaluated wood is indicated for structural uses according to the C40 class (NBR 7190-1997). Finally, DIC was able to adequately provide displacement values that occurred during tests, enabling the modulus of elasticity calculation. Keywords: wood characterization, non-destructive method, physical and mechanical properties, strain.